2014
DOI: 10.3344/kjp.2014.27.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Nefopam for the Treatment of Neuropathic Pain

Abstract: Nefopam (NFP) is a non-opioid, non-steroidal, centrally acting analgesic drug that is derivative of the non-sedative benzoxazocine, developed and known in 1960s as fenazocine. Although the mechanisms of analgesic action of NFP are not well understood, they are similar to those of triple neurotransmitter (serotonin, norepinephrine, and dopamine) reuptake inhibitors and anticonvulsants. It has been used mainly as an analgesic drug for nociceptive pain, as well as a treatment for the prevention of postoperative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 44 publications
0
91
0
3
Order By: Relevance
“…nefopam during phase 1, but not during phase 2, of a formalin test (47). Furthermore, it has been confirmed in an in vivo animal pain model that monoamine depletion inhibited nefopam antinociception, which indicated the involvement of neuromediators in nefopam-induced analgesia (6). More recently, a number of studies have been conducted on the receptor subtypes that are involved in nefopam antinociception.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…nefopam during phase 1, but not during phase 2, of a formalin test (47). Furthermore, it has been confirmed in an in vivo animal pain model that monoamine depletion inhibited nefopam antinociception, which indicated the involvement of neuromediators in nefopam-induced analgesia (6). More recently, a number of studies have been conducted on the receptor subtypes that are involved in nefopam antinociception.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, it effectively elicits antinociception in the majority of noxious and thermal models in rodents (3,4). The mechanisms of action of nefopam may involve inhibition of monoamine reuptake in the central nervous system and glutamatergic pathway, in which calcium channels serve a role (5,6). Certain adverse reactions of nefopam, including dizziness, headache, nausea, vomiting and sweating, have been associated with its central mechanisms (7).…”
Section: Introductionmentioning
confidence: 99%
“…elucidated [11,18,19]. Studies of serotonin receptor antagonists reported that ondansetron and palonosetron were effective in the prevention of rocuronium-induced withdrawal response [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Nefopam has several potential adverse events, including sedation, dry mouth, tachycardia, dizziness, sweating, nausea and vomiting, dysphoria, diplopia, and dizziness [11,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation